Concept Understanding and Mathematic Problem Solving Skills in Algebraic Materials: the Effect Of Dragonbox Game Assisted DMR Of Covid-19 - Supriadi, Nanang; Ramadona, Kartika; Pratiwi, Dona Dinda; Widyawati, Santi (Al-Jabar: Jurnal Pendidikan Matematika, 2020)
This article aims to find out how the ability to understand concepts and solve mathematical problems of junior high school students in Bandar Lampung after being treated using Multy Reprecentacy Discourse learning (DMR) assisted by dragonbox games for one semester of learning. Data analysis was based on an assessment of 64 students (experimental class n = 32 and control class n = 32) using the One-way Multivariate Analysis of Variance (MANOVA) analysis technique. The results showed that significantly learning during the Covid-19 pandemic using the DMR model assisted by mathematics games had a better effect on students' understanding of concepts and solving mathematical problems partially or simultaneously.